HDAC3 maintains oocyte meiosis arrest by repressing amphiregulin expression before the LH surge - Huarong Wang (Nature Portfolio, 2019)
Before ovulation, a surge of luteinizing hormone (LH) triggers the resumption of meiosis in oocytes, which is mediated by EGF-like growth factors. Here, the authors show that HDAC3 inhibits mouse oocyte maturation by negatively regulating the expression of EGF-like factor before the LH surge.